Trends in type 2 diabetes prevalence according to income levels in Korea (1998–2012). (May 2016) - Ko, B.; Lim, J.; Kim, Y.Z.; Park, H.S.
Highlights: We examined trends in prevalence of type 2 diabetes in Korea according to income. Gender difference in relationship between income and diabetes prevalence aggravated. High income level in men positively related to the odds of diabetes. And women with low income had an increased likelihood of diabetes. Prevention for diabetes should consider gender-specific economic discrepancy. Abstract: There was no significant association between diabetes prevalence and income levels for either sex in 1998. However, the high income level in men and the low income level in women positively related to the odds of diabetes in 2011–2012. Preventive strategies for diabetes should consider the gender-specific economic discrepancy